Level of soil contamination with arsenic and heavy metals in Tiquillaca (Peru) - Fernandez Ochoa, Benito Hugo (2022)
The Andes plays an important role in the providing of ecosystem services, however, the greatest threat it faces today is soil contamination by heavy metals, which constitutes a risk in the interaction of man and the environment, in this understanding it is necessary to promote research in the mountainous region in activities that contravene the sustainable development of the region. In this sense, the objective of this study is to evaluate the level of soil contamination by heavy metals by means of the geo-accumulation index and to predict the influence of pH and organic matter on the distribution of metals in the soil. The methodology involved the extraction of four soil samples obtained in an area adjacent to the Paxa stream, where mining waste was dumped; the total concentration of Arsenic, Barium, Cadmium, Copper, Chromium, Lead, Nickel and Zinc was evaluated by the optical emission spectrophotometry method, pH and organic matter by potentiometry and colorimetry, respectively. The results showed geo-accumulation indices for As, Cd, and Pb with moderately to heavily contaminated (class 1, 2 and 3, respectively).In contrast, soils were not contaminated with Ba, Cr, Cu, Ni and Zn (class 0), which represents a risk for the Andean ecosystem, given the acidic characteristics of the soil (4.08) and minimum organic matter content (0.9%), which will promote the solubility and mobility of heavy metals in the ground.